PENGARUH PEMBERIAN ARANG SEKAM DAN PUPUK ORGANIK CAIR DARI LIMBAH BUAH DAN SAYUR TERHADAP PERTUMBUHAN BIBIT GAHARU (Aquilaria malaccensis) - Rizka Ayu Wahyuli Sanaky; Ludia Siahaya; Febian Tetelay (MARSEGU : Jurnal Sains dan Teknologi, 2024)
This study aims to determine the effect of applying husk charcoal and liquid organic fertilizer from fruit and vegetable waste in increasing the growth of agarwood seedlings (Aqualaria malaccensis). This research was carried out in the Nursery of the Department of Forestry, Faculty of Agriculture, Pattimura University for three months. The method used in this study is a Complete Random Design (RAL) with 2 factors and 3 replicates. The first factor is the dose of liquid organic fertilizer from fruit and vegetable waste consisting of 4 levels, namely A0 (No liquid organic fertilizer), A1 (100 ml), A2 = (200 ml), A3 = (300 ml) The second factor is the application of husk charcoal consisting of 2 levels, namely B1 (No husk charcoal), B2 (Husk charcoal). The results showed that A1B2 treatment (100 ml POC + husk charcoal medium) gave the highest results on plant height, A2B1 (200 ml POC + no husk charcoal media) gave the highest results on plant diameter, while the highest number of leaves was A0B1 (control + no husk charcoal).